Effects of doxorubicin and ibrutinib on atrial arrhythmogenity: ex-vivo assessment in human myocardium. (3rd October 2022) - Berger, Y; Primessnig, U; Huettemeister, J; Parwani, A S; Boldt, L H; Pieske, B; Falk, V; Grubitzsch, H; Blaschke, F; Heinzel, F R
Abstract: Introduction: The cytostatic drugs doxorubicin (Dox) and ibrutinib (Ibr) are established in the treatment of various tumor diseases. In (pre-) clinical studies, both chemotherapeutic agents showed cardiotoxic side effects, including atrial fibrillation [1]. In this context, patients with limited cardiac performance or diabetes might be particularly vulnerable, as these pre-existing conditions represent independent risk factors for cardiac complications [2]. Objectives: The dose-dependency of acute pro-arrhythmogenic effects of Dox and Ibr on the contractile activity of human atrial muscle tissue was investigated. Patients and methods: Atrial samples were taken intraoperatively during cardiac procedures. Functional muscle strips were prepared from the cardiac trabeculae, followed by incubation with different concentrations of Dox or Ibr for 30 minutes. Subsequently, functional measurements were performed. Isometric contraction force and arrhythmogenic occurrences were recorded. The samples were consecutively exposed to external stressors during measurement (Fig. 1). We evaluated the overall occurrence of arrhythmogenic contractions and during which phase of the protocol they occurred. The latter was expressed as degree of arrhythmogenesis (Fig. 1). Following the functional measurements, the muscle strips were conserved at −80°C. Results: We isolated 127 muscle strips from 29 patients. Highest rates of overall arrhythmic contractions were observed at 10μM Dox and 0.5μM Ibr (77.8 & 100% vs. 58.4% (control)). Mean degree of arrhythmogenesis increased from 1.63 (control) to 2.17 (10μM Dox) and 3.11 (0.5μM Ibr). Analyzing our data according to the included individuals, treatment with Dox and Ibr enhanced the degree of arrhythmogenesis in the majority of patients. (Fig. 2) Conclusion: Our protocol is suitable for investigating drug related acute pro-arrhythmogenic effects on human atrial myocardium. Treatment of isolated atrial myocardium with Dox and Ibr enhanced its susceptibility to arrhythmogenic occurrences. Optimal pro-arrhythmogenic conditions were observed at 10μM Dox and 0.5μM Ibr. The treated samples showed higher overall rates of arrhythmogenic contractions and the arrhythmogenic activity occurred earlier within our protocol. Outlook: We will correlate the experimentally obtained data with clinical patient data, such as LVEF, BMI and diabetic status. The conserved muscle strips will be analyzed using standardized assays comparing post-translational modification (e.g. phosphorylation and oxidation) of key regulators of excitation contraction coupling (e.g. PKA, CaMKII, Ca2+ channels). Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): DZHK (German Centre for Cardiovascular Research), partner site Berlin